2016
DOI: 10.1038/srep32639
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Performance Limitations of Lithium-ion Batteries due to Species and Charge Transport through Five Characteristic Parameters

Abstract: Underutilization due to performance limitations imposed by species and charge transports is one of the key issues that persist with various lithium-ion batteries. To elucidate the relevant mechanisms, two groups of characteristic parameters were proposed. The first group contains three characteristic time parameters, namely: (1) te, which characterizes the Li-ion transport rate in the electrolyte phase, (2) ts, characterizing the lithium diffusion rate in the solid active materials, and (3) tc, describing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 59 publications
0
92
0
Order By: Relevance
“…Although, increasing the electrode thickness significantly enhances the specific capacity of the electrode up to approximately 100 µm, theoretical [19,[29][30][31][32][33][34] and experimental [35][36][37][38] results clearly show that large electrode thicknesses lead to low rate capability originating from Li + diffusion limitations in the electrolyte. For example, the conductive additive content can be increased until limitations of the electron transport in the composite become negligible.…”
mentioning
confidence: 95%
“…Although, increasing the electrode thickness significantly enhances the specific capacity of the electrode up to approximately 100 µm, theoretical [19,[29][30][31][32][33][34] and experimental [35][36][37][38] results clearly show that large electrode thicknesses lead to low rate capability originating from Li + diffusion limitations in the electrolyte. For example, the conductive additive content can be increased until limitations of the electron transport in the composite become negligible.…”
mentioning
confidence: 95%
“…Nevertheless, the Li-ion transport limitations in liquid electrolytes become increasingly important as the electrode thickness increases 67,68,70,71 because the diffusion time in the liquid phase is no longer negligible as a result of the significant increase in diffusion length in the thick porous electrodes. Consequently, it is necessary to design thick electrode architectures to take advantage of the increased energy density provided by the higher active material volume ratio, while minimizing the tortuosity and transport limitations that can be detrimental to power performance.…”
Section: Electrode Engineeringmentioning
confidence: 99%
“…Many different designs have been suggested, including graded-porosity and hierarchical architectures, 67,[72][73][74][75][76] and several simulations have shown that smaller active material particles can help decrease the polarization and capacity loss observed at high discharge rates by shortening the Li-ion diffusion path in the particles. 68,71,77 Yet, particle size variations also affect the packing structure of the electrode and can result in different pore sizes and distributions, as well as in differences in the contact resistance between the electrode and the current collector. These variations could be leveraged to improve transport properties and battery performance.…”
Section: Electrode Engineeringmentioning
confidence: 99%
“…The first rapid decline is in response to the fast decreasing SOC; for the 4 mΩ case, the discharge current is too large, making this period too short to observe. In the middle period, the discharge process is limited by the lithium transport in the electrolyte or in solid active materials . Regarding the last instant drop period, we speculate it is caused by the destroyed or blocked Li‐ion transmission pathways in the battery inside rather than the disconnection of electricity circuit.…”
Section: Resultsmentioning
confidence: 94%
“…In the middle period, the discharge process is limited by the lithium transport in the electrolyte or in solid active materials. 14,20,21 Regarding the last instant drop period, we speculate it is caused by the destroyed or blocked Li-ion transmission pathways in the battery inside rather than the disconnection of electricity circuit. The high temperature (Figure 3 C) may arouse some abusive reactions of the battery materials (several reactions are involved for an overheated cell) inside the battery, which consume some battery materials or destroy the internal structure.…”
Section: Effects Of Esc Resistancementioning
confidence: 97%